The Role of Price Discounts in Moderating, Customer Reviews and Free Shipping on Shopee Purchase Decisions in Surabaya - Muhammad Rosyihuddin; Joni Hendra (Dinasti Review, 2022)
Abstract: Along with technological developments, the world of marketing has now changed. Studying E-consumer behavior from a renewable aspect is needed to create practical and efficient marketing, research that refers to digital marketing (Digital Marketing), especially the E-Marketing marketplace. This study examines online consumer behavior that focuses on purchasing decisions and renewable factors that influence it, namely: customer reviews and the promotional tagline